2006
DOI: 10.1016/j.geoderma.2005.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Burning effects on the distribution of organic N compounds in a 15N labelled forest soil

Abstract: Nitrogen distribution was studied, by successive 1M (H1) and 3M HCl (H2) hydrolyses, on a natural soil before (NS) and after 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
(60 reference statements)
3
25
0
Order By: Relevance
“…Wildfires modify quantitatively and qualitatively the soil C and N pools (Castro et al 2006;Certini et al 2011;Fernández et al 1997Fernández et al , 1999 that are the energy source for heterotrophs and the substrate for N transformations, respectively. Although weak relations have also been reported (Gómez-Rey et al 2012), the soil C and N pools are considered to be important controlling factors of gross N transformations (Booth et al 2005;Lang et al 2010;Magill and Aber 2000), with which they showed moderate to strong correlations in our plots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfires modify quantitatively and qualitatively the soil C and N pools (Castro et al 2006;Certini et al 2011;Fernández et al 1997Fernández et al , 1999 that are the energy source for heterotrophs and the substrate for N transformations, respectively. Although weak relations have also been reported (Gómez-Rey et al 2012), the soil C and N pools are considered to be important controlling factors of gross N transformations (Booth et al 2005;Lang et al 2010;Magill and Aber 2000), with which they showed moderate to strong correlations in our plots.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all samples and incubation intervals together, two thirds of in variance was explained by a model with the initial NO 3 Introduction Fires, either natural or anthropic, can strongly impact the biogeochemical cycles of nutrients; their effects are especially important for N which, besides being the major growthlimiting element since the evolution of higher plants (Ericsson 1995), is also the nutrient most prone to particulated and gaseous losses during the fires (Certini 2005;Fisher and Binkley 2000). Moreover, fires modify the dynamics of the soil N (a) by decreasing the most labile pools and increasing the most recalcitrant ones (Castro et al 2006;Prieto-Fernández et al 1993, 2004, partly by immobilising heterocyclic N into neoformed stable polyaromatic compounds that persist in soils (Francioso et al 2011;Knicker 2007;Mastrolonardo et al 2014), and (b) by affecting the N transformations that, as microbially mediated processes, are modified through changes in enzymatic activities and in biomass and composition of soil microbiota (Barreiro et al 2010;Díaz-Raviña et al 2012).…”
mentioning
confidence: 99%
“…Charring often results in only small changes (Czimczik et al, 2003;Knicker et al, 2005a) or a decrease (Baldock and Smernik, 2002;Harden et al, 2004;Neff et al, 2005) in the C/N ratio, and an increase in more recalcitrant organic N forms (González-Pérez et al, 2004;Castro et al, 2006). In SOM unaffected by fire, 15 N NMR indicates that amide is the predominant form of soil N, whereas an increase of pyrroletype N is found in fire-affected soils, and has been suggested as a molecular marker of fire (Knicker et al, 2005a).…”
Section: How Fire Affects Soil Properties and Developmentmentioning
confidence: 99%
“…Fire significantly affects the availability of nutrients, especially nitrogen (N) Rau et al 2007). Over the long term, fire can lead to losses in total N through volatilisation and through transfer of organic N from labile to recalcitrant pools (Gonzalez-Perez et al 2004;Castro et al 2006). Also, fire can negatively impact microbial biomass and activity that, in turn, can slow the cycling of plant-available N (Choromansk and DeLuca 2002;Certini 2005;Guerrero et al 2005).…”
Section: Introductionmentioning
confidence: 99%